The effect of exercise on innate mucosal immunity. Issue 4 (22nd May 2008) - West, N P; Pyne, D B; Kyd, J M; Renshaw, G M; Fricker, P A; Cripps, A W
Abstract : Methods: The authors conducted a prospective observational study comparing salivary lactoferrin and lysozyme concentration over 5 months (chronic changes) in elite rowers (n=17, mean age 24.3±4.0 years) with sedentary individuals (controls) (n=18, mean age=27.2±7.1 years) and a graded exercise test to exhaustion (acute changes) with a cohort of elite rowers (n=11, mean age 24.7±4.1). Results: Magnitudes of differences and changes were interpreted as a standardised (Cohen's) effect size (ES). Lactoferrin concentration in the observational study was approximately 60% lower in rowers than control subjects at baseline (7.9±1.2 µg/ml mean±SEM, 19.4±5.6 µg/ml, p=0.05, ES=0.68, 'moderate') and at the midpoint of the season (6.4±1.4 µg/ml mean ± SEM, 21.5±4.2 µg/ml, p=0.001, ES=0.89, 'moderate'). The concentration of lactoferrin at the end of the study was not statistically significant (p=0.1) between the groups. There was no significant difference between rowers and control subjects in lysozyme concentration during the study. There was a 50% increase in the concentration of lactoferrin (p=0.05, ES=1.04, 'moderate') and a 55% increase in lysozyme (p=0.01, ES=3.0, 'very large') from pre-exercise to exhaustion in the graded exercise session. Conclusion: Lower concentrations of these proteins may be indicative of an impairment of innate protection of the upper respiratory tract. Increased salivary lactoferrin and lysozyme concentration following exhaustive exercise may be due to a transient activation response that increases protection in the immediate postexercise period.